2022
DOI: 10.15244/pjoes/152224
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH on the Particulate-Bound Cd Speciation and Uptake by Plants

Abstract: The speciation of heavy metals in soil is a better indicator for assessing the bioavailability than the total concentration. Soil pH is a vital factor influencing the particulate-bound metal speciation and the metal dynamics at rhizosphere soil-root interface. In this study, greenhouse pot experiment was conducted to reveal the influence of pH on the speciation of cadmium (Cd) in solid phase of soil and the amount of Cd uptake by different ecotype plants. The results illustrated that the exchangeable Cd decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The decrease in soil pH was observed in all soil Cd treatments in intercropping. The ndings of our study align with previous research, which demonstrated that a decrease in soil pH leads to an increase in the bioavailability of Cd (Lian et al, 2022) and is the key reason for the greater root Cd uptake and higher Cd concentration in aboveground plant parts (Tsadilas et al, 2005;Zou et al, 2023). Bian et al (2021) found that intercropping bamboo and Sedum plumbizincicola led to an increase in biomass and a decrease in soil pH, which facilitated the removal of heavy metals from the soil.…”
Section: Intercropping Enhanced Plant Biomass By Modulating Photosynt...supporting
confidence: 90%
“…The decrease in soil pH was observed in all soil Cd treatments in intercropping. The ndings of our study align with previous research, which demonstrated that a decrease in soil pH leads to an increase in the bioavailability of Cd (Lian et al, 2022) and is the key reason for the greater root Cd uptake and higher Cd concentration in aboveground plant parts (Tsadilas et al, 2005;Zou et al, 2023). Bian et al (2021) found that intercropping bamboo and Sedum plumbizincicola led to an increase in biomass and a decrease in soil pH, which facilitated the removal of heavy metals from the soil.…”
Section: Intercropping Enhanced Plant Biomass By Modulating Photosynt...supporting
confidence: 90%
“…Soil pH is a critical factor influencing HMs' chemical speciation and bioavailability in the CS [ 26 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the incubation experiment, although initially the entire set of soils used exhibited the CFeO-Cd fraction as the predominant fraction within inorganic Cd fractions, it was observed that OM-Cd and Res.-Cd contained the least Cd fraction (Figure 1). Numerous studies have demonstrated the influence of various soil physicochemical properties such as soil texture, organic matter content, and pH on the distribution of inorganic Cd fractions in soils (Anju and Banerjee, 2011;Nejad et al, 2021;Lian et al, 2022). Kızılkaya and Aşkın (2002), in their investigation of the distribution of Cd fractions and the relationships between soil properties in agricultural fields in the Bafra Plain of Turkey, determined that the total Cd content in alluvial soils ranged from 1.83 to 2.73 mg kg -1 .…”
Section: Resultsmentioning
confidence: 99%